Examination on antioxidant activity in the greater celandine (Chelidonium majus L.) extracts by FRAP method - Then, Mária (Acta Biologica Szegediensis, 2003)
Antioxidant activity in the alcoholic extracts (20 and 40%) of the greater celandine (Chelidonium majus L.) herb was investigated by FRAP (ferric reducing and antioxidant power) method. Since the antioxidant activity of the extracts greatly depends on the quality of compounds, the phytochemical examination for alkaloid- and element content were also examined. According to the results the antioxidant activity does not depend on the alkaloid content of the drug during the vegetation period and on the alkaloid content of the alcoholic extracts. It seems that the antioxidant activity of the extracts is also independent from the transition metal element content.